Fertilizer-bioinsecticide synergy improves maize resilience to Spodoptera frugiperda infestation - Fiaboe, K.R.; Agboka, K.; Agnamba, A.O.; Teyo, K.L.; Amegah, A.L.; Koffi, D.; Kpadonou, G.E.; Agboka, K.M.; Gwokyalya, R.; Fening, K.O.; Fiaboe, K. (Elsevier, 2024)
Fall armyworm (FAW), Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae), invasion in Africa has threatened food security. Optimization of plant tolerance and post-infestation recovery are among the management tactics that are being promoted for the integrated management of this pest, but these techniques are poorly studied in sub-Saharan Africa. Our study examined the efficacy of enriched compost, split-NPK fertilization, conventional fertilization, and bioinsecticides on FAW infestation rates, maize plant resilience, natural enemy presence, and grain yield. We found that split-NPK fertilization significantly improved maize plant robustness and reduced FAW incidence and leaf damage in a phenology-dependent manner, leading to higher grain yields. A synergistic effect was observed when split-NPK was coupled with bioinsecticides, resulting in increased populations of natural predators, and specifically the egg endoparasitoid, Telenomus remus (Nixon) (Hymenoptera: Scelionidae). Multivariate analyses confirmed that factors like split-NPK fertilization, bioinsecticide usage, stem circumference, and overall plant robustness are major determinants of maize grain yield. Our results endorse soil fertility management via split-NPK fertilization as an effective cultural control measure against FAW, providing an alternative to synthetic insecticides. These insights set the stage for future research focused on assessing the economic viability of this integrated approach, exploring the integration of split-NPK with alternative insecticides, evaluating environmental impacts, and examining the underlying resilience mechanisms to FAW, among other avenues.